2004
DOI: 10.1016/s0014-5793(03)01508-4
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient renaturation of β‐lactamase isolated from moderately halophilic bacteria

Abstract: Most, if not all, L L-lactamases reported to date are irreversibly denatured at 60^70 ‡C. Here, we found that a halophilic L L-lactamase from the moderately halophilic bacterium Chromohalobacter sp. 560 was highly stable against heat inactivation: it retained V V75% of its activity after boiling for 5 min in the presence of 0.2 M NaCl, suggesting that the protein either incompletely denatures during the boiling process or readily renatures upon cooling to the assay temperature. Circular dichroism showed a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 28 publications
(44 reference statements)
0
42
0
Order By: Relevance
“…The halophilic bacterium used was strain 160, which was isolated from a seashore specimen (Matsushima, Japan). The physiological properties and nucleotide sequence of the 16S rRNA gene (accession number AB105069) suggested that this strain belongs to the genus Chromohalobacter, and it was found to be identical to strain 560, which was used previously (29). Cells were grown at 37°C in nutrient broth (NB; 1% beef extract and 1% polypeptone, pH 7.0) supplemented with 2 M NaCl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The halophilic bacterium used was strain 160, which was isolated from a seashore specimen (Matsushima, Japan). The physiological properties and nucleotide sequence of the 16S rRNA gene (accession number AB105069) suggested that this strain belongs to the genus Chromohalobacter, and it was found to be identical to strain 560, which was used previously (29). Cells were grown at 37°C in nutrient broth (NB; 1% beef extract and 1% polypeptone, pH 7.0) supplemented with 2 M NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…This plasmid was introduced into Chromohalobacter sp. strain 160, and Sm r integrants were selected on SW-8 plates (32) containing 0.5 mg of streptomycin/ml (29).…”
Section: Methodsmentioning
confidence: 99%
“…These fusion partners are normally either N-or C-terminally fused to the target gene, as an expression vector, with a protease cleavage sequence. We have shown before that a novel halophilic ␤-lactamase (BLA) is an ideal candidate as a fusion partner, since it is relatively small and highly soluble in aqueous solution [8,9]. In fact, the BLA was found to enhance soluble expression of recombinant human interleukin-1␣ and human serine racemase, both of which otherwise tend to form IBs when expressed in E. coli [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the property described above, one of the most characteristic features that are shared by many halophilic proteins is the high solubility of the proteins both in the native and unfolded states [8,28,29,33,34]. High solubility of unfolded structure in aqueous buffer solution is the most critical parameter that plays a major role in its refolding efficiency.…”
mentioning
confidence: 99%